The Turkish version of the Nursing Teamwork Survey: A validity and reliability study. Issue 3 (11th September 2020) - Taskiran Eskici, Gulcan; Baykal, Ulku
Abstract: Aim: This study aimed to test the validity and reliability of the Turkish version of the Nursing Teamwork Survey, which was developed to measure the concept of nursing teamwork. Method: Performed as a methodological study with a cross‐sectional design, the study included 486 bedside nurses in three different types of hospitals in Istanbul. The data were collected using the Nursing Teamwork Survey between October and December 2018. The scale includes five subscales and 33 items. The data were analysed using SPSS 22.0 and LISREL 8.7. Results: Nurses' mean age was 29.82 ( SD = 7.33). The content validity index of the scale was 0.94. Confirmatory factor analysis conducted on the original form showed that all items fell within the subscales of the original scale and that their factor loads were between 0.48 and 0.91. Following factor analysis, the factor structure of the original scale was valid; however, suggested modifications were applied to improve the results. The obtained goodness‐of‐fit indices were close to the excellent range according to literature. Cronbach's alpha was 0.95 for the scale. Conclusion: The scale is a valid and reliable tool for measuring teamwork among nurses. SUMMARY STATEMENT: What is already known about this topic? Teamwork between nurses is a critical issue for patient and nurse outcomes in health care. Well‐performing teams make fewer mistakes than those of individuals who work alone. Nonfunctional teams lead to conflicts and absenteeism and decrease performance and job satisfaction. What this paper adds? The Turkish version of the Nursing Teamwork Survey has been validated. In the absence of a valid and reliable tool to measure nurses' teamwork, this can now be measured with this tool. The implications of this paper: Nurse managers can use this tool to measure teamwork process between nurses.